ANALISIS PERBANDINGAN METODE EOQ DAN METODE POQ DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PD. SINAR RAHAYU - Nur Sany, Yansa; Sofyab, Hady; Nur Amalia, Akhsani (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
There are various efforts that companies can make to maintain company sustainability, one way that companies can do this is by optimizing the procurement of raw materials. By purchasing optimal raw materials, the company will of course obtain maximum profits and be able to maintain the company's continuity so that the company's survival can be guaranteed. The aim of this research is to determine the application of the EOQ and POQ methods in controlling raw materials for skin crackers, determining safety stock and inventory costs. In this research, the data analysis technique used is descriptive statistical analysis by collecting data, analyzing data, and describing the data obtained for comparison between the method of controlling the supply of skin crackers in Sinar Rahayu with the Economic Order Quantity (EOQ) inventory method. control method, and Economic Order Quantity (EOQ) method. Period Order Quantity (POQ) inventory control .EOQ 296kg orders 23 times a year, buffalo hide 226 kg 18 times a year. Sefetystock cowhide 54kg, buffalo 31kg. Total EOQ costs Rp. Rp. 3,254,504, buffalo leather Rp. 2,486,324. POQ cowhide 285 kg with a frequency of 24 times, buffalo skin 166 kg with a frequency 28 times a year. Safety stock POQ is the same as POQ. The total price of POQ cowhide is IDR 3,410,149.80 and the total price of buffalo leather is IDR 3,949,193. The lowest inventory costs are obtained using the EOQ method. The EOQ method can be an option for controlling leather raw material supplies in PD. Ray of Rahayu.